Solvent polarity-driven phytochemical profiling and antioxidant evaluation of Indian Persimmon (Diospyros kaki Thunb.) fruit extracts - Singarayar, Magdalin Sylvia; Chandrasekaran, Ajithan; Neethirajan, Vivek; Balasundaram, Dhivyadharshini; Veerasamy, Veeramurugan; Thilagar, Sivasudha (Journal of Phytology, 2025)
The present study investigates the phytochemical composition and antioxidant potential of Indian Persimmon (Diospyros kaki Thunb.) extracts obtained using ten different solvents with varying polarity. Soxhlet extraction was employed to obtain the extracts, with hydroethanolic solvent yielding the highest extractable content. Qualitative phytochemical screening revealed the presence of key bioactive compounds, including flavonoids, phenolics, alkaloids, terpenoids, saponins, tannins and significant levels of sugar across all extracts. Quantitative estimations indicated that Acetone extract of D. kaki (7.23±0.5 mg GAE/g) and Ethyl acetate extract of D. kaki (4.54±0.01 mg QE/g) were particularly rich in total phenolics and flavonoids, while Aqueous extract of D. kaki (1016±0.36 mg GE/g) and Hydroethanol extract of D. kaki (1015±0.79 mg GE/g) exhibited higher carbohydrate content. Uronic acid and reducing sugar levels were also prominent in the Acetone extract of D. kaki (395.14±0.32 & 1255±2 mg GluA/g), suggesting efficient extraction of pectic and simple sugar fractions. Antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging assays. Among the tested extracts, Ethyl acetate extract of D. kaki (28.96 & 33.19 μg/mL) and Acetone extract of D. kaki (127.6 & 18.43 μg/mL) demonstrated notable antioxidant capacities, with IC50 values closely approaching that of the standard BHT in both assays. These findings underscore the influence of solvent polarity on phytochemical recovery and bioactivity, with mid-polar solvents proving most effective in extracting antioxidant constituents. The results highlight D. kaki fruit as a promising natural source of antioxidants with potential therapeutic applications, particularly in managing oxidative stress-related disorders such as colon cancer.